THE EFFECT OF INQUIRY TRAINING MODELS USING INTERACTIVE MULTIMEDIA TOWARD STUDENTS LEARNING OUTCOMES - Muhammad Iman Hidayat; Yuna Sutria (Jurnal Pendidikan Fisika, 2019)
This research aims to determine the effect of inquiry training models using interactive multimedia to the physics learning outcomes students of SMA Negeri 21 Medan. Samples were taken using the probability sampling where the experimental classes were applied to the inquiry training models using interactive multimedia while the control class implemented direct instructional models. The instruments used in this study consist of 10 questions that are validated using the validity of the contents. The data on this research is quantitative data. Data analysis techniques for testing the hypothesis used in this research use SPSS with the use of different pairs of tests. The results showed that the learning outcomes students with the inquiry training model using interactive multimedia are better than the student learning outcomes taught with the direct instructional models.